THE THE EFFECTIVNESS OF MULLIGAN MOBILIZATION AND INFRARED WITH MYOFASCIAL RELEASE TECHNIQUE AND INFRARED TO IMPROVE RANGE OF MOTION OF NON-SPESIFIC NECK PAIN ON TAILOR IN THE SUBDISTRIC KUTA - Wahyuningsih, Ni Wayan; Wahyuni, Nila; Adiputra, Luh Made Indah Sri Handari (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Non-spesific neck pain is one of disorder among general population including tailors in Subdistric Kuta. Therefore the need for a therapy that can be given as myofascial release technique, mulligan mobilization, and infrared. The design of this study was experimental with pre-test and post-test group design. The technique sampling was purposive sampling technique. The samples were divided into 2 groups. Group 1 was given Myofascial Release Technique and Infrared, while Group 2 was given Mulligan Mobilization and Infrared. The range of motion is measured by goniometer. The result showed no significant difference between Group 1 and Grpu[ 2 in which p value = 0.250 (p>0.05) with 56.8% in the Group 1 and 60.8% in the Group 2. Based on result , it can be concluded that Myofascial Release Technique and Infrared show no significant difference with Mulligan Mobilization and Infrared to increase range of motion of the neck on the non-spesific neck pain. Keywords : non-spesific neck pain, myofascial release technique, mulligan mobilization, infrared.